2022
DOI: 10.1155/2022/9681769
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Intelligent Medical Data Technology in Postoperative Nursing Care

Abstract: Surgery is one of the larger wounds in conventional surgery, and patients often experience different pain and postural discomfort after surgery. With the ever-changing standards of medical care and patient care requirements, providing high-quality care to postoperative patients is an important measure to reduce complications and promote rapid recovery. However, in the traditional postsurgical nursing methods, there are often the phenomenon that wrong patients are connected, patient data is messy, and medicines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In recent years, there has been a significant shift toward the extensive utilization of various computer science techniques, including machine learning, deep learning, neural networks, and artificial intelligence. Duan and Lin (2022) integrated big data and Internet of Things technology to assess the impact of intelligent medical data analysis technology on postoperative nursing efficiency, with the aim of transforming conventional postoperative care practices. This reflects the growing integration of sophisticated computational methods to gain deeper insights into patient outcomes and healthcare practices in the nursing field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a significant shift toward the extensive utilization of various computer science techniques, including machine learning, deep learning, neural networks, and artificial intelligence. Duan and Lin (2022) integrated big data and Internet of Things technology to assess the impact of intelligent medical data analysis technology on postoperative nursing efficiency, with the aim of transforming conventional postoperative care practices. This reflects the growing integration of sophisticated computational methods to gain deeper insights into patient outcomes and healthcare practices in the nursing field.…”
Section: Discussionmentioning
confidence: 99%
“…For instance,Sterling et al (2019) employed natural language processing technology and neural network model training to predict the prognosis of emergency patients using data from emergency triage records. Additionally, Monsen et al (2017) leveraged big data and visualization technology to enhance the quality of care provided during home visits by public health nurses.In recent years, there has been a significant shift toward the extensive utilization of various computer science techniques, including machine learning, deep learning, neural networks, and artificial intelligence Duan and Lin (2022). integrated big data and Internet of Things technology to assess the impact of intelligent medical data analysis technology on postoperative nursing efficiency, with the aim of transforming conventional postoperative care practices.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%